(untitled) (Biological Sciences - PJSIR, 2000)
To enhance the rate of multiplication of Polianthes tuberosa, in vitro techniques were applied. The micropropagation potential of bulb and leaf tissues was explored. Twin scale and chip cxplants from .the lower halves and single scale explants from the upper halves of the bulbs were cultured on MS medium supplemented with diIferent concentrations of naphthalene acetic acid (NAA) and benzyl aminopurinc (BAP). bulblet induction was pronounced on both twin scales and chips. Bulblet formation and gain in size was greater inthe case of chips than in twin scales, indicating an influence of the size of the explant. Bulblet induction on single scale explants oftuberose bulbs was also observed. Leaf blade explants formed callus on MS medium supplemented with defined hormonal concentrations of BAP, *AA and Kin. Psuedoernbryogenic bodies regenerated from the calli.